Inorganic Elements of Mangium Stem (Acacia mangium Willd) from Different Provenanc - Ganis Lukmandaru; Vendy Eko Prasetyo; Widyanto Dwi Nugroho (Wood Research Journal, 2015)
This study aimed to investigate the ash content and concentrations of inorganic elements present in the stem of Acacia mangium. The tree samples (24 years) were collected from five different provenances (Sidei, West of Morehead, Daintree, Ellerbeck, and El Arish). Meanwhile, the disc samples were obtained from the trunk of each tree on the lower parts. The samples were collected from four radial positions (bark, sapwood, outer heartwood, inner heartwood), and the ash and insoluble acid contents were determined. Furthermore, the concentration of 5 elements (Ca, Mg, Fe, Mn, K, and Na) was measured by Atomic Absorption Spectrophotometry (AAS). The interaction of provenance and radial position factors affected ash and potassium contents. Also, acid insoluble ash and calcium contents showed a provenance factor effect. The barks obtained from the tree samples contained the highest concentrations of ash content and most of the elements. The wood and bark of El-Arish provenance showed the lowest (0.50~0.72%) and highest levels (4.75%) of ash content respectively. Furthermore, the highest amount of insoluble acid ash (3075 ppm) and calcium (4513 ppm) content was also measured in samples of El-Arish provenance, and radial position factor was a significant source of variation for Ca, Mg, Na, and Mn concentrations. Except Mg, the inner and outer portions of the heartwood mostly showed no significant difference in unprecedented element concentrations. Ash content was positively correlated with Ca in sapwood (r=0.39) and Mn in bark (r=0.54). In addition, moderate correlations were observed between Mg and Ca in heartwood (r=0.63) and bark (r=0.54) tissues. For ash and silica content, the comparatively low concentration on samples from El-Arish provenance are good options to improve wood quality for breeding programs.